Effect of polyamines on thermal inactivation of hen egg white lysozyme - Nobakht Motlagh Ghochani, Bi Bi Fatemeh; Moosavi-Nejad, Seyedeh Zahra; Ordibehesht, Seyed Ashkan (Archives of Advances in Biosciences, 2013)
Lysozyme is considered as part of the innate immune system. It has stimulated considerable interest as a natural food preservative. Lysozyme has been shown to be effective in preserving a variety of foods such as fresh fruits and vegetables, meats, seafood and wine, for which many Japanese patents have been granted. The relatively high thermal stability of lysozyme also makes it attractive for use in pasteurized and heat-sterilized food products, possibly allowing reduced thermal processes, and therefore, minimized nutritional and sensory quality loss. In this study, we investigated effect of polyamines on the thermal inactivation of lysozyme by kinetics curves. Our results showed that polyamines can decrease the thermal inactivation of lysozyme; the effect of spermine on the thermal inactivation of lysozyme was more than that of the spermidine.